Analysis of Influence on The Level of The Economy, Knowledge of Taxes, and Sanctions on Compliance with Land and Building Tax Payments in Rural and Urban Areas (PBB-P2) - Refi Pratiwi; Mas Iman Kusnandar (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2021)
The purpose of this study was to determine and analyze the level of the economy, knowledge of taxes, and sanctions on compliance with land and building tax payments in rural and urban areas (PBB-P2) for the people of Cadasari District, Pandeglang Regency. This research uses a quantitative approach. The data source used in this study is primary data; this research was taken by distributing questionnaires to the respondents, namely land and building taxpayers in Cadasari District, Pandeglang Regency. The data analysis method used in this study is multiple linear regressions (Multiple Regression Analysis). This analysis is intended to reveal the influence between several independent variables and the dependent variable. The population in this study was the people of Cadasari District who were registered as land and building taxpayers (PBB-P2) at the end of 2020, namely 2417 people, while the sample using Slovin’s formula was determined as many as 44 samples. The results of the research on the hypothesis that part there is an influence on the level of the economy, knowledge of taxes and sanctions on compliance with the payment of Rural and Urban Land and Building Tax (PBB-P2) for the people of Cadasari District, Pandeglang Regency.